Parboiled rice supplementation alleviates high-fat diet-induced hyperlipidemia by regulating genes and gut microbiota in mice - Xiuxiu Wu; Tianyi Guo; Biao Li; Shuai Han; Zuomin Hu; Yi Luo; Dandan Qin; Yaping Zhou; Feijun Luo; Qinlu Lin (Food Science and Human Wellness)
Dietary parboiled rice (PR) has a low risk of disease, but little is known about the contribution of PR to the prevention of hyperlipidemia. The potential role and underlying mechanisms of PR in hyperlipidemia were evaluated in this study. Male C57BL/6J mice were fed with a normal diet, high-fat diet (HFD) containing refined rice (HFDRR) or PR (HFDPR). It was found that PR intervention improved lipid accumulation in mice. Transcriptomic data analysis revealed that 27 genes were up-regulated (mostly involved in lipid breakdown) and 86 genes were down-regulated (mostly involved in inflammatory responses) in the HFDPR group compared to the HFDRR group. And 15 differentially expressed genes (DEGs) were validated by quantitative real-time PCR (RT-qPCR), while protein interaction network showed that protein tyrosine phosphatase receptor type C (PTPRC) has a central role. The gut microbiota of mice was also altered after different dietary treatments, with higher ratio of Firmicutes and Bacteroidetes, increased abundances of Ruminococcaceae, Lachnospiraceae, Christensenellaceae, Porphyromonadaceae, Rikenellaceae and Prevotellaceae, and decreased abundances of Lactobacillaceae, Peptostreptococcaceae, Erysipelotrichaceae and Actinobacteria in the HFDRR group. In addition, it was observed that PPAR signaling pathway may act as a bridge between DEGs and differential gut microbiota. These results suggested that PR can prevent hyperlipidemia by modulating liver genes and gut microbiota.